Inclusion of Waste Paper on Concrete Properties: A Review - B. A. Solahuddin; F. M. Yahaya (Civil Engineering Journal, 2021)
The environmental degradation in the vicinity of landfills or mills is caused by waste paper disposable. Each year, the industry's paper waste is increasing gradually. As a result, additional places are required for landfills, which consume energy, deplete natural resources, and increase expenditure and environmental pollution. Pollution can be reduced by adding WP to a concrete mixture in concrete production. This review paper investigates the physical and chemical properties of waste paper. Besides that, the mechanical properties of concrete containing waste paper, such as compressive, flexural, and splitting tensile strengths, are also studied in this review paper. All reviews of the intended studies include experimental tests. From the reviews, all strengths were increased with the inclusion of waste paper, either by addition, substitution, or replacement with fine aggregate, coarse aggregate, or cement. By using waste paper, not only would concrete have advantages and benefits, but also environmentally friendly construction materials could be produced from time to time. It has been noted in most studies that the inclusion of waste paper brings significant benefits. It can be concluded that waste paper potentially has favorable properties for concrete production. The concrete performance will improve in terms of compressive, flexural, and splitting tensile strengths with waste paper inclusion at certain percentages compared to ordinary concrete with no waste paper content. Doi: 10.28991/CEJ-SP2021-07-07 Full Text: PDF